2019
DOI: 10.1016/j.ygcen.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fecal hormones for noninvasive research on reproduction and stress in humpback whales (Megaptera novaeangliae)

Abstract: Fecal hormone analysis shows high potential for noninvasive assessment of population-level patterns in stress and reproduction of marine mammals. However, the marine environment presents unique challenges for fecal sample collection. Data are still lacking on collection methodology and assay validations for most species, particularly for those mysticete whales that have variable diets. In this study we tested collection techniques for fecal samples of free-swimming humpback whales (Megaptera novaeangliae), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 65 publications
3
22
0
Order By: Relevance
“…However, we were able to provide a physiologic validation of our FGCM assay system by detecting significantly increased hormone concentrations during pregnancy as compared to non-pregnant females and males. This agrees with circulating GC and excreted GCM changes that have been documented during pregnancy in other cetaceans [29,41,43,60,61]. In addition, and as would be expected, we saw increased concentrations during the mid and late pregnancy stages compared to the early stage, and concentrations significantly increased during the final months prior to parturition (Table 3, Figure 1B).…”
Section: Fgcm Concentrations Biological Validationsupporting
confidence: 90%
See 1 more Smart Citation
“…However, we were able to provide a physiologic validation of our FGCM assay system by detecting significantly increased hormone concentrations during pregnancy as compared to non-pregnant females and males. This agrees with circulating GC and excreted GCM changes that have been documented during pregnancy in other cetaceans [29,41,43,60,61]. In addition, and as would be expected, we saw increased concentrations during the mid and late pregnancy stages compared to the early stage, and concentrations significantly increased during the final months prior to parturition (Table 3, Figure 1B).…”
Section: Fgcm Concentrations Biological Validationsupporting
confidence: 90%
“…This limitation has led to the use of less invasive methods for determining an animal's allostatic state by relying on fecal GC metabolic products in multiple terrestrial species (see review of FGCM studies [39]) and a few cetacean species [6,7,34,40,41]. FGCM concentrations are influenced by pregnancy and/or parturition in BDs [41], humpback whales (Megaptera novaeangliae) [42,43] and blue whales (Balaenoptera musculus) [44]. A study in the North Atlantic right whale (Eubalaena glacialis) has demonstrated that FGCM concentrations are influenced by loud vessel noise or by animal entanglement in fishing gear [40,42,44].…”
Section: Introductionmentioning
confidence: 99%
“…Roles for regulation of these pathways via post-translational deimination have not been investigated. Thyroid hormones have been studied in a range of whales and dolphins, including for evaluation of energetics and stress Hunt et al, 2019), as well as environmental pollution (Buckmann et al, 2011;Villanger et al, 2011;Hunt et al, 2017;Simond et al, 2019). PADs have been related to thyroid cancer (Guo et al, 2017) and deimination of histone H3 has been linked to autoimmune thyroid disease (Morshed et al, 2019), while physiological effects of deimination on thyroid hormone synthesis remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…To address these challenges, methods for remote biopsy sampling (e.g. via a dart attached to a pole or deployed by crossbow) of marine mammals and hormone detection in a variety of other matrices, such as blubber, respiratory vapor and feces, have been actively developed ( Boggs et al , 2017 , Burgess et al , 2017 , Burgess et al , 2018 , Champagne et al , 2017 , Hunt et al , 2019 , Noren et al , 2012 ). However, hormone measurements often lack the sensitivity to identify recent exposure to a stressor and do not provide additional information on downstream consequences.…”
Section: Introductionmentioning
confidence: 99%